Indonesian gen Z consumer preference for subscribing to netflix in the Covid-19 pandemic era / Pijar Suciati and Barijani Mahesa Putra - Suciati, Pijar; Putra, Barijani Mahesa (Universiti Teknologi MARA, 2022)
During the Covid 19 pandemic, people are quarantined and children are not allowed to attend school. They are optimizing the internet in order to obtain amusement. One of the most common ways to pass the time and occupy oneself is to watch movies online. Netflix has been the most popular movie online streaming platform in Indonesia since 2016. The goal of this study is to learn about the preferences of Generation Z (Gen Z) consumers when it comes to subscribing to Netflix amid the Covid-19 pandemic. This research is explanatory and descriptive with mixed method approach. Purposive sampling using criteria is used to select the sample size, and the survey is conducted using a Google Form with 100 respondents. One of the findings suggests that Gen Z is more likely to choose Netflix premium (52 %) due to its extensive features and high quality. The qualitative findings corroborate the quantitative findings. Netflix's service and movie selections are rated highly by respondents. The practical value of this research is that it provides some information about the Gen Z consumer's favorite genre and behavior in Indonesia to the online streaming sector.